Hypoxia/reoxygenation of rat renal arteries impairs vasorelaxation via modulation of endothelium-independent sGC/cGMP/PKG signaling - Braun, Diana; Schubert, Rudolf (Frontiers in physiology, 2018)
Ischemia/reperfusion injury holds a key position in many pathological conditions such as acute kidney injury and in the transition to chronic stages of renal damage. We hypothesized that besides a reported disproportional activation of vasoconstrictor response, hypoxia/reoxygenation (H/R) adversely affects endothelial dilatory systems and impairs relaxation in renal arteries. Rat renal interlobar arteries were studied under isometric conditions. Hypoxia was induced by application of 95% N2, 5% CO2 for 60 min to the bath solution, followed by a 10 min period of reoxygenation (95% O2, 5% CO2). The effect of H/R on relaxation was assessed using various inhibitors of endothelial dilatory systems. mRNA expression of phosphodiesterase 5 (PDE5), NADPH oxidases (NOX), and nitric oxide synthase (NOS) isoforms were determined using qRT-PCR; cGMP was assayed with direct cGMP ELISA. Acetylcholine induced relaxation was impaired after H/R. Inhibition of the NOS isoforms with L-NAME, and cyclooxygenases (COX) by indomethacin did not abolish the H/R effect. Moreover, blocking the calcium activated potassium channels KCa3.1 and KCa2.1, the main mediators of the endothelium-derived hyperpolarizing factor, with TRAM34 and UCL1684, respectively, showed similar effects in H/R and control. Arterial stiffness did not differ comparing H/R with controls, indicating no impact of H/R on passive vessel properties. Moreover, superoxide was not responsible for the observed H/R effect. Remarkably, H/R attenuated the endothelium-independent relaxation by sodium nitroprusside, suggesting endothelium-independent mechanisms of H/R action. Investigating the signaling downstream of NO revealed significantly decreased cGMP and impaired relaxation during PDE5 inhibition with sildenafil after H/R. Inhibition of PKG, the target of cGMP, did not normalize SNP-induced relaxation following H/R. However, the soluble guanylyl cyclase (sGC) inhibitor ODQ abolished the H/R effect on relaxation. The mRNA expressions of the endothelial and the inducible NOS were reduced. NOX and PDE5 mRNA were similarly expressed in H/R and control. Our results provide new evidence that impaired renal artery relaxation after H/R is due to a dysregulation of sGC leading to decreased cGMP levels. The presented mechanism might contribute to an insufficient renal reperfusion after ischemia and should be considered in its pathophysiology.
Gesehen am 05.08.2019